Relative and cumulative effects of lipid and blood pressure control in the stroke prevention by aggressive reduction in cholesterol levels trial - Amarenco, Pierre; Goldstein, Larry B.; Messig, Michael; O'Neill, Blair J.; Callahan, Alfred; Sillesen, Henrik; Hennerici, Michael G.; Zivin, Justin A.; Welch, K. M. A. (Stroke, 2009)
BACKGROUND AND PURPOSE: The relative contributions of on-treatment low- and high-density lipoprotein cholesterol (LDL-C, HDL-C), triglycerides, and blood pressure (BP) control on the risk of recurrent stroke or major cardiovascular events in patients with stroke is not well defined. - METHODS: We randomized 4731 patients with recent stroke or transient ischemic attack and no known coronary heart disease to atorvastatin 80 mg per day or placebo. - RESULTS: After 4.9 years, at each level of LDL-C reduction, subjects with HDL-C value above the median or systolic BP below the median had greater reductions in stroke and major cardiovascular events and those with a reduction in triglycerides above the median or diastolic BP below the median showed similar trends. There were no statistical interactions between on-treatment LDL-C, HDL-C, triglycerides, and BP values. In a further exploratory analysis, optimal control was defined as LDL-C <70 mg per deciliter, HDL-C >50 mg per deciliter, triglycerides <150 mg per deciliter, and SBP/DBP <120/80 mm Hg. The risk of stroke decreased with as the level of control increased (hazard ratio [95% confidence interval] 0.98 [0.76 to 1.27], 0.78 [0.61 to 0.99], 0.62 [0.46 to 0.84], and 0.35 [0.13 to 0.96]) for those achieving optimal control of 1, 2, 3, or 4 factors as compared to none, respectively. Results were similar for major cardiovascular events. - CONCLUSIONS: We found a cumulative effect of achieving optimal levels of LDL-C, HDL-C, triglycerides, and BP on the risk of recurrent stroke and major cardiovascular events. The protective effect of having a higher HDL-C was maintained at low levels of LDL-C.